Public or private job placement services — Are private ones more effective? - Gesine Stephan (IZA World of Labor, 2024)
Contracting out job placement services might save costs and provide a service capacity buffer in times of increasing unemployment. However, state agencies must be able to ensure a suitable balance between services and quality, and to carefully monitor and evaluate private provider outcomes. Empirical evidence finds that public employment agencies are at least equally as successful in placing the unemployed as private providers. Conditions for successful implementation include the conclusion of complete contracts, adequate monitoring of quantity and quality, low entry barriers into the market, and longer-term development processes.
Keywords: L33; J68; J65; H44; H53; 330; unemployment; employment services; privatization; contracting out